Shooting STAR: reinterpreting the data from the 'Single Embryo TrAnsfeR of Euploid Embryo' randomized clinical trial. Issue 4 (April 2020) - Pagliardini, Luca; Viganò, Paola; Alteri, Alessandra; Corti, Laura; Somigliana, Edgardo; Papaleo, Enrico
Abstract: Preimplantation genetic testing for aneuploidy (PGT-A) still remains controversial in clinical practice. Recently, the randomized controlled trial, 'Single Embryo TrAnsfeR of Euploid Embryo' (STAR) by Munné and coworkers showed a similar live birth rate per intention to treat in the two study groups (PGT-A and controls). A wrong diagnosis and/or biopsy-related damage to the embryo might underlie these results. To assess the impact of these factors on the efficiency of PGT-A, the live birth rate of 'euploid' embryos transferred in the PGT-A group was compared with its ideal value, namely the live birth rate of embryos with the potential to implant and to give rise to a baby in the control group. This estimate has been derived using the results of the genetic testing reported in the STAR trial. According to this model, the STAR trial has demonstrated that transferring only blastocysts classified as 'euploid' after PGT-A leads to a reduction from 82.2% to 50.0% of the live birth rate for competent embryos, thus supporting the idea that PGT-A is associated with some embryo wastage.